Demokratyczna legitymizacja prawa – tworzenie i stosowanie prawa (zarys problemu) - Bekrycht, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2016)
The aim of the article by the way of introduction is a sketching out some remarks from a perspective of philosophy of law concerning the contemporary crisis, which currently take place in many countries in Europe and in the EU. The author claims that the discussions and disputes over the nowadays European crisis is based on out-of-date paradigm presumptions such as legal positivism and post-totalitarian models of law. To solve the disputes the author proposes reflection based on conception of a communication model of law and community citizens’ idea.